Neonatal Volkmann Ischemic Contracture: Case Report and Review of Literature - Hitesh Agrawal; Gunjan Dokania; Shou-Yien Wu (Thieme Medical Publishers, Inc., 2014)
Abstract Background Neonatal Volkmann ischemic contracture in newborns is a devastating condition with lifelong consequences. Case Report We report a neonate born with necrotic skin lesions and bullae on right dorsal thenar aspect of hand, who subsequently developed compartment syndrome requiring fasciotomy. Review and Conclusion Necrotic skin lesions with/without swelling, bullae are invariably present at birth in these patients and should be recognized as a sentinel finding of underlying tissue ischemia/compartment syndrome. Early recognition and prompt surgical intervention can be limb saving. A range of radiologic abnormalities and contractures were noted in upto 84% of such patients followed long term. Hence, we recommend close follow-up until occurrence of epiphyseal fusion in these patients.